2008
DOI: 10.3354/dao01947
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carp intestinal mucus molecular size and glycosylation on bacterial adhesion

Abstract: The first step of the pathogenesis of many infectious diseases is the colonisation of the mucosal surface by the pathogen. Bacterial colonisation of the mucosal surface is promoted by adherence to high molecular weight mucus glycoproteins. We examined the effect of carp intestinal mucus glycoproteins on the adhesion of different bacteria. The bacteria used were 3 strains of Aeromonas hydrophila, and A. salmonicida, Edwardsiella tarda and Yersinia ruckeri. All bacteria adhered to mucus, but at varying intensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Luminal mucin might be essential for protection of the intestinal surface, as higher bacterial adhesion to smaller mucus molecules has been observed (Schroers et al . ). Mucin degradation by pathogenic bacteria has been suggested earlier for C. carpio (Van der Marel et al .…”
Section: Discussionmentioning
confidence: 97%
“…Luminal mucin might be essential for protection of the intestinal surface, as higher bacterial adhesion to smaller mucus molecules has been observed (Schroers et al . ). Mucin degradation by pathogenic bacteria has been suggested earlier for C. carpio (Van der Marel et al .…”
Section: Discussionmentioning
confidence: 97%
“…Other possible changes in the cellular architecture and composition of the digestive tract might favour parasite entrance and proliferation in the intestinal epithelium, through changes at the host-parasite interface (Yoshino et al, 2001), alterations of the gut barrier or the mucosal immunity (Kasper and Buzoni-Gatel, 2001), or alterations of the biochemical makeup of the cell membrane lipid rafts/caveolae microdomains (Chapkin et al, 2008). In fact, the effect of PLs, FAs and soybean meal on tight-junction permeability and therefore in bacterial translocation (Sawai et al, 2001), on fish intestinal mucus and bacterial adhesion (BakkeMcKellep et al, 2007;Schroers et al, 2008) have been reported. Thus, further studies are needed to determine the effect of vegetable diets in the distribution and composition of enzymes, other molecules of interest and leucocyte populations in the intestinal tract.…”
Section: Discussionmentioning
confidence: 98%
“…Different bacterial species groups bind to different N-glycan epitopes [62], [63]. Therefore, a change in glycosylation of the mucosa can influence the binding of bacteria to it.…”
Section: Discussionmentioning
confidence: 99%